A functional preservation strategy for the production of highly photoluminescent emerald carbon dots for lysosome targeting and lysosomal pH imaging. Issue 30 (24th July 2018) - Zhang, Qian Qian; Yang, Tong; Li, Rong Sheng; Zou, Hong Yan; Li, Yuan Fang; Guo, Jian; Liu, Xi Dong; Huang, Cheng Zhi
Abstract : Emerald carbon dots prepared at room temperature can actively target lysosomes owing to their amino groups from a functional preservation strategy (FPS). Abstract : Lysosomes, which can be easily targeted by molecules with abundant amino groups, play critical roles in endocytosis, autophagy, and phagocytosis; thus, it is important to accurately characterize lysosomes, including lysosomal pH, in living cells to understand their physiological and pathological functions. Herein, a new type of highly photoluminescent (PL) emerald carbon dots (CDs) was easily prepared through a functional preservation strategy (FPS) by simply mixing p -benzoquinone and ethanediamine at room temperature. The as-prepared CDs possessed abundant amino groups preserved from ethanediamine owing to FPS, and they exhibited excellent photostability as compared to the commercial LysoTracker probes. Consequently, they actively targeted lysosomes to sensitively respond to lysosomal pH in vitro owing to their abundant amino groups and good hydrophilicity. Thus, we could successfully monitor lysosomal pH dynamics during apoptosis in live cells.